The Habit of “Let's Write Cheerfully” for Children Aged 5-6 Years Old - Monitasari, Aprillia; Katoningsih, Sri (Early Childhood Research Journal (ECRJ), 2021)
Aim This research is early childhood as someone who is just starting the stage of development in the world with various experiences that children get. Children have their own weaknesses and strengths where the weaknesses and strengths of the child need to be considered and then developed according to their talents. This research can be a source to motivate children aged 5-6 years to like writing as a way of preparing themselves to enter school to the next level. Method is research articles from several "databases" using certain keywords in the period 2003-2020. There are 13 national journal articles and 5 international journal articles that meet the criteria in these keywords. The results showed that writing activities for early childhood can be done in various ways such as writing with comics, writing with pictorial media, writing with the obstacle course method so that learning to write becomes more effective and children become more cheerful in developing their fine motor skills in the field of writing.